IMPLEMENTASI METODE MUSTAQILLI DALAM MENINGKATKAN HASIL BELAJAR BAHASA ARAB SISWA-SISWI MTS MAMBAUL ULUM - Khotimah, Isnol; Muthmainnah, Inni (At- Ta'lim : Jurnal Pendidikan, 2024)
This study aims to provide solutions to the problem of Arabic learning at MTS Mambaul Ulum, where students tend to consider Arabic subjects as foreign and less interesting due to monotonous curriculum, less attractive teaching methods, and inappropriate use of educational media. As a solution, the Arabic teacher decided to apply the Mustaqilli method in the first grade of MTS Mambaul Ulum. This study used a descriptive qualitative approach involving 98 students. Data are obtained through interviews, observation, and documentation. Data analysis was carried out with data condensation stages to analyze the results of observations, interviews, and documentation related to the implementation of the Mustaqilli method. The results showed that the implementation of the Mustaqilli method was able to increase student activeness in learning Arabic. The learning process is carried out at 07.00-09.00 WIB, with emphasis on the importance of learning Arabic and reading the book without harokat. The formal findings of the implementation of the Mustaqilli Method are able to create an active, fun learning atmosphere, and provide positive results for students' progress in understanding and practicing Arabic.